Can non-functional adrenal incidentaloma be ranked among cardiovascular risk factors? - Yağız, Burcu; Akalın, Aysen; Yorulmaz, Göknur; Macunluoğlu, Aslı Ceren; Yağız, Onur (The European Research Journal, 2022)
Objectives: We aimed to evaluate the potential association of a nonfunctional adrenal incidentaloma (NFAI) with cardiovascular risk factors. Methods: Forty-three patients over the age of 40 found to have NFAI and 28 healthy controls were included in this prospective study. The control group was selected from individuals who were similar in age and gender. Glucose, insulin, c-peptide, lipid profile, erythrocyte sedimentation rate, high sensitivity c-reactive protein, fibrinogen and 25-hydroxy cholecalciferol and carotid artery intima-media thickness (CIMT) were measured in both groups. Results: Waist circumference, erythrocyte sedimentation rate, triglyceride and CIMT values were found higher in the patient group (p = 0.002, p < 0.001, p = 0.001, p = 0.024, respectively). It was observed that 10 (23.2%) of the patients had no suppression with 1 mg dexamethasone but suppression was provided with 2 mg dexamethasone for 2 days, and all of these patients with ‘possible autonomous cortisol secretion’ had at least one comorbidity. While there was no significant difference between the groups in terms of the presence of comorbidity, a significant difference was found in terms of diabetes mellitus (90% of the patients with autonomous cortisol secretion, 24.2% of those who were suppressed with 1 mg dexamethasone had diabetes mellitus; p < 0.001; Chi-square test). Conclusions: Higher waist circumference, erythrocyte sedimentation rate, triglyceride and CIMT values in our patients with NFAI and increased diabetes mellitus frequency in patients with autonomous cortisol secretion suggest that NFAI may be one of the cardiovascular risk factors.